Upaya Meningkatkan Aktifitas dan Hasil Belajar Bahasa Indonesia Pokok Bahasan Teks Cerita (Novel) Sejarah dengan Menggunakan Model Pembelajaran STAD Siswa Kelas XII IPS 1 SMAN 3 Kotabumi Tahun Pelajaran 2018-2019 - ida wati (Universitas Muhammadiyah Kotabumi, 2020)
This study aims to increase the activities and outcomes of Indonesian language learning by using the STAD learning model in historical text material (novels) of class XII IPS 1 students of SMA Negeri 3 Kotabumi in the 2018-2019 academic year. This classroom action research used students of XII IPS 1 SMA Negeri 3 Kotabumi as research subjects. In practice, it was carried out to test the effect of learning historical story text material (novel) by practicing the STAD type cooperative learning model on student learning outcomes. The research was carried out in 2 cycles, namely for the material structure, content, value and language of historical story texts (novels) and elements, topics and frameworks of historical story texts (novels) where all cycles began with planning activities followed by implementation and observation and ended with reflection. . Data collection techniques using cognitive tests and student attitude questionnaires obtained from each cycle, the results were analyzed whether there was an increase in each cycle. After conducting research and data analysis, the results obtained were an increase in student learning outcomes and activities from cycle I to cycle II. For indicators of student learning outcomes there was an increase of 58% in cycle II when compared to cycle I. Meanwhile, for student activities in disciplinary indicators there was an average increase of 0.7, for indicators of cooperation the average increase was 1.05, indicators of courtesy. The average score was 0.56 and for the tolerance indicator the average increase was 1.16 and overall for student learning activities increased by 20.47. The conclusion of this study is that the application of the STAD learning model to historical text material (novels) can increase the activities and learning outcomes of Indonesian students in class XII IPS 1 at SMAN 3 Kotabumi in the 2018-2019 academic year.